Con Mis Hijos No Te Metas: a study of discourse and power in a Peruvian Facebook group opposing «gender ideology» - Meneses, Daniela (2019)
In 2016, a national campaign against the Ministry of Education’s new National Curricula for Basic Education emerged in Peru. A Facebook group with the name «Con Mis Hijos No Te Metas PERÚ-Oficial» («Don’t Mess With My Children PERU-Oficial», in English) also appeared. It started receiving thousands of «likes» and was used to share information about the curricula and coordinate activities and protests. In the context of this campaign, I conducted a netnography of the Facebook group and analyzed the discourse that appears in the page. Using Foucault’s ideas of power as a point of departure, I argue that religious individuals that oppose the curricula and participate in the page are exercising pastoral power, and acting like pastors in charge of guiding a flock of bodies-souls away from this «gender ideology» and to salvation. I explore how pastors also exercise disciplinary power (seeking to normalize heterosexual bodies-souls) and biopower (hoping to assure the reproduction of mankind by making people engage only in heterosexual sex). I show how both these powers are reconfigured through pastoral power and have salvation as its aim. I also explore how God exercises sovereign power through the pastors, condemning to Eternal Damnation the LGBTQI* individuals that don’t follow his path and that accept the «gender ideology» being imposed in schools. I argue that this exercise of sovereign power is legitimized through pastoral power. Finally, I maintain that the specific configuration of sovereign power in the Facebook group can be understood as an instance of necropower.